Pengaruh Financial Literacy dan Income Terhadap Personal Financial Management Behavior pada Mahasiswa Prodi Akuntansi Universitas Medan Area - Sibarani, Annisa Raudhatul Jannah; Amelia, Wan Rizca (Universitas Medan Area, 2024)
This research aims to explore the impact of Financial Literacy and Income on the Personal Financial Management Behavior of Accounting students and students at Medan Area University. This research is a type of associative research with a quantitative approach. The sample in this research were students from the Faculty of Economics and Business, Stambuk 2020 Accounting Study Program, Medan Area University, totaling 67 samples using a sampling technique, namely purposive sampling with criteria, namely students from the Faculty of Economics and Business, Accounting study program. Data collection was used using questionnaire methods, documentation studies and interviews. Data analysis uses multiple linear regression analysis, hypothesis testing, classical assumption testing, and coefficient of determination test (R2). The results of the research show that 1) Financial Literacy has a positive and significant influence on Financial Management Behavior, 2) Income has a positive and significant influence on Financial Management Behavior, 3) Financial Literacy and Income simultaneously have a positive and significant influence on the Financial Management Behavior of Class students 2020 Medan Area University Accounting study program.